Directorio de exportadores de Cuba = Directory of Cuban exporters 2004-2005 - Navas, Pérez, Olena (CEPEC HavanaCU, 2004)
Contains up to date information on Cuban export companies, as well as key data on the economic, commercial and financial spheres.